Diagnostic Value of Sputum Eosinophil Counts in Patients with Cough Variant Asthma - Hossain, SK Shahinur; Islam, Md. Safiul; Rahman, Md. Mustafizur; De, Shubhashish (Bangladesh Journal of Infectious Diseases, 2017)
Background: Diagnosis of cough variant asthma is very important. Objectives: The purpose of the present study was to measure the diagnostic value of eosinophil counts in sputum for the diagnosis of cough variant asthma patients. Methodology: This descriptive type of cross-sectional study was carried out in the Department of Respiratory Medicine at National Institute of Diseases of the Chest and Hospital (NIDCH), Dhaka, Bangladesh from September 2014 to August 2015 for a period of one year. Patients presented with cough variant asthma attending in NIDCH were selected as study population. Methacholine challenge test was performed to diagnosis of cough variant asthma. After Methacholine test, patient was encouraged to produced sputum. Sputum was collected in a plastic container and labeled accordingly and was sent to microbiology department of NIDCH for sputum eosinophil counts. Result: A total number of 50 patients were recruited for this study. The mean age±SD was found 19.1±7.6 years. 20 patients had leucocytosis. 96% patients had sputum eosinophil, 90% patients had >3% sputum eosinophil and 10% patients had ?3% sputum eosinophil count. All patients had trigger factor with negative CFT for Filaria and increased serum IgE. Conclusion: In conclusion increased eosinophil count in sputum is diagnostic tool in cough variant asthma. Bangladesh Journal of Infectious Disease 2015;2(2):37-41